Design and Analysis of a Micro–Electro-Mechanical System Thruster for Small Satellites and Low-Thrust Propulsion - Yubin Zhong; Fabrizio Ponti; Francesco Barato; Guojun Xia; Siyu Li; Xiao Zhang; Tao Wu (Aerospace)
As a cost-effective and versatile solution, small satellites are increasingly being considered for space exploration. However, one of the major challenges in deploying small satellites for high total impulse missions, particularly deep space exploration, lies in the propulsion system. These missions face strict constraints in terms of volume, mass, and power budgets. This paper proposes a potential solution to this issue through the design of a bipropellant MEMS thruster. Simulation results indicate that this type of thruster offers superior performance compared to the monopropellant propulsion systems typically used in small satellite missions. Specifically, the bipropellant MEMS thruster demonstrates enhanced specific impulse and thrust-to-weight ratio, making it a promising alternative for small satellite propulsion in high total impulse missions.